Detection of single bacteria – causative agents of meningitis using raman microscopy. (18th March 2015) - Baikova, T V; Minaeva, S A; Sundukov, A V; Svistunova, T S; Bagratashvili, V N; Alushin, M V; Gonchukov, S A
Abstract: Early diagnostics of meningitis is a very topical problem as it is a fulminant disease with a high level of mortality. The progress of this disease is, as a rule, accompanied by the appearance of bacteria in the cerebrospinal fluid (CSF) composition. The examination of the CSF is well known to be the only reliable approach to the identification of meningitis. However, the traditional biochemical analyses are time consuming and not always reliable, simple, and inexpensive, whereas the optical methods are poorly developed. This work is devoted to the study of Raman spectra of several bacterial cultures which are mainly present during meningitis. Raman microscopy is a prompt and noninvasive technique capable of providing reliable information about molecular-level alterations of biological objects at their minimal quantity and size. It was shown that there are characteristic lines in Raman spectra which can be the reliable markers for determination of bacterial form of meningitis at a level of a single bacterium.